Advances in Cryptology - EUROCRYPT 2016 35th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Vienna, Austria, May 8-12, 2016, Proceedings, Part I - Fischlin, Marc; Coron, Jean-Sébastien (Security and Cryptology ;, 2016)
The two-volume proceedings LNCS 9665 + LNCS 9666 constitutes the thoroughly refereed proceedings of the 35th Annual International Conference on the Theory and Applications of Cryptographic Techniques, EUROCRYPT 2016, held in Vienna, Austria, in May 2016. The 62 full papers included in these volumes were carefully reviewed and selected from 274 submissions. The papers are organized in topical sections named: (pseudo)randomness; LPN/LWE; cryptanalysis; masking; fully homomorphic encryption; number theory; hash functions; multilinear maps; message authentification codes; attacks on SSL/TLS; real-world protocols; robust designs; lattice reduction; latticed-based schemes; zero-knowledge; pseudorandom functions; multi-party computation; separations; protocols; round complexity; commitments; lattices; leakage; in differentiability; obfuscation; and automated analysis, functional encryption, and non-malleable codes.